Centralized Strategies for Grid-Connected Microgrids Integrating Multicontrol Actions to Enhance the Dynamic Response - Joao Marcus S. Callegari; Lucas S. Chaves; Lucas S. Araujo; Braz J. Cardoso Filho; Danilo I. Brandao (IEEE Open Journal of the Industrial Electronics Society)
Feedback, feedforward, and disturbance decoupling control actions are commonly addressed to the well-known current control of distributed energy resources (DERs). This article extends these control actions to centralized grid-connected microgrids (MGs) aiming to improve the dynamics at their point of common coupling (PCC). Three strategies are comprehensively compared considering 1) feedback action (F control); 2) feedforward and disturbance decoupling actions (fD control); and 3) all three actions (FfD control). Time-varying experimental results obtained using an experimental laboratory-scale single-phase MG show the feasibility of these centralized control schemes in real-field applications. Comparison is carried out regarding the PCC power reference tracking, MG control dynamic stiffness, and stability evaluation related to communication link nonidealities. Among the strategies, F and fD controls show lower susceptibility to communication latency. The proposed complete strategy, i.e., FfD, shows wider reference tracking bandwidth and increased low-frequency dynamic stiffness to load and communication disturbances. These enhanced capabilities are attained by properly applying the well-established control actions at the MG firmware level, without requiring any MG hardware retrofit.